The viral and inflammation hypothesis of epileptic seizures based on bioinformatic study of circulating miRNAs and peripheral whole-blood mRNAs of adult epilepsy patients - Wu, Jiahuan; Meng, Ying; Xu, Fei; Wu, Qian; Wang, Cheng (Frontiers in Neurology, 2022)
Background The study aimed to investigate the genome-wide biological significance of the circulating miRNAs markers found in peripheral whole blood of adult epileptic seizures patients by integrating analysis using bioinformatics approaches. Methods The Gene Expression Omnibus (GEO) dataset was accessed to retrieve epilepsy-related circulating miRNA profile data (GSE114847) including 89 subjects (n = 40 epileptic and n = 49 healthy control), peripheral whole-blood mRNA expression data (GSE143772) including 64 subjects (n = 32 epileptic and n = 32 healthy control). To eliminate age disparities in epilepsy pathophysiology only adult epileptic patients were selected. Furthermore, GEO2R was used to identify adult-related mRNAs (AD-mRNAs) against epilepsy as potential biomarkers. Moreover, to predict the potential target genes for these mRNAs, we used mirWalk. Finally, the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were utilized to investigate the biological activities of AD-mRNAs. Importantly, the protein–protein network of these identified AD-mRNAs was constructed. Eventually, the overlapping AD-mRNAs and AD-miRNAs and their functions were explored to shortlist potential AD-epileptic markers. Result The current study resulted in the identification of 79 upregulated and 40 downregulated different expression gene (DEGs) in both applied data. These targets were cross-linked and mapped with each other to acquire common adult epilepsy-related overlapped mRNAs (Mo-mRNAs). It was found that there was a total of 36 overlapping genes. These overlapped AD-mRNAs markers were found to be functionally enriched in cell regulating pathways i.e., positive regulation of type 1 interferon signaling pathway and mitochondrial cytochrome C release pathway, respectively. Conclusion This research gives a comprehensive depiction of the mRNAs that may be involved in adult epilepsy patients' pathophysiological progressions.